The Effect of Depression and Cognitive Function on the Geriatric Oral Health Assessment Index in the Elderly - Sun-Mi Kim; Young-Im Kim (치위생과학회지, 2022)
Background: Depression and cognitive function have a positive effect on the improvement of quality of life and extension of lifespan in the elderly. In addition, it appears as a major factor influencing oral health status. Therefore, this study looked at the relationship between the Geriatric Oral Health Assessment Index (GOHAI), depression, and cognitive function in the elderly using the Korea Longitudinal Study of Aging.Methods: In this study, 4,535 elderly people aged 65 years and over were targeted using the 7th data of the 2018 Korea Longitudinal Study of Aging. A t-test and ANOVA analysis were performed to compare GOHAI, depression, and cognitive function by group. In addition, hierarchical multiple linear regression was performed to understand the effect of the elderly’s perceived depression scale and cognitive ability on GOHAI.Results: As a result of adding the depression scale and cognitive function variables to Model 2, the explanatory power was 22%. Educational level, marital status, private health insurance subscription, average monthly allowance, subjective health status, use of dentures, smoking status, economic activity, depression scale, and cognitive function were found to have significant influence (p＜0.05). In addition, when controlled and viewed with all factors, depression and cognitive function were found to have an effect on oral health-related quality of life.Conclusion: The findings indicate that depression and cognitive function are associated with oral health-related quality of life in the Korean elderly. As the age increases, the quality of life declines due to depression and cognitive function problems, in addition to oral discomfort, eating disorders, and physical discomfort.